2013
DOI: 10.1111/ele.12181
|View full text |Cite
|
Sign up to set email alerts
|

Individual personalities predict social behaviour in wild networks of great tits (Parus major)

Abstract: Social environments have an important effect on a range of ecological processes, and form a crucial component of selection. However, little is known of the link between personality, social behaviour and population structure. We combine a well-understood personality trait with large-scale social networks in wild songbirds, and show that personality underpins multiple aspects of social organisation. First, we demonstrate a relationship between network centrality and personality with 'proactive' (fast-exploring) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
356
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(372 citation statements)
references
References 47 publications
14
356
2
Order By: Relevance
“…This conforms with the well-supported theoretical expectation that 'proactive' (i.e. bold, aggressive, fast-exploring) individuals tend to have lower sociability and weaker social network associations [9,31,60]. Alternatively, this pattern may reflect either BTdependent spatial preferences (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This conforms with the well-supported theoretical expectation that 'proactive' (i.e. bold, aggressive, fast-exploring) individuals tend to have lower sociability and weaker social network associations [9,31,60]. Alternatively, this pattern may reflect either BTdependent spatial preferences (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…These effects may explain variation in the spatial distribution of BTs (e.g. why similar BTs are clumped together in some cases but not in others; [58]), in their interaction rates and overall social network positions [60].…”
Section: Discussionmentioning
confidence: 99%
“…This method has already been successfully applied in several studies of this population (e.g. Farine et al 2012;Aplin et al 2013).…”
Section: Closing Remarksmentioning
confidence: 99%
“…Researchers have simply assumed that the same collective movement rules apply to any conspecifics detected within an individual's perceptual zone (Couzin et al, 2002;Hemelrijk & Hildenbrandt, 2008). Yet, empirical work has shown that phenotypic assortment and social preferences for particular individuals influence animal grouping patterns (e.g., Griffiths & Magurran, 1997;Croft et al, 2009;Aplin et al, 2013). Incorporating such preferences-embodied within a group's social network-into models of collective motion and decision-making will help to generate new, testable predictions for the field (Bode et al, 2011a).…”
Section: Collective Movement and Decision-makingmentioning
confidence: 99%
“…Personality types have been shown to differ in the strength and distribution of their interactions with group members and to assort with others based on personality (e.g., Pike et al, 2008;Croft et al, 2009;Aplin et al, 2013). Some personality types can occupy prominent or influential network positions, thereby wielding disproportionate influence over network dynamics compared to other group members (Flack et al, 2006;Modlmeier, Keiser, et al, 2014).…”
Section: Animal Personalitiesmentioning
confidence: 99%